Infectious complications, steroid use and timing for emergency liver transplantation in acute liver failure: analysis in a Japanese center. (6th October 2016) - Yasui, Shin; Fujiwara, Keiichi; Haga, Yuuki; Nakamura, Masato; Mikata, Rintaro; Arai, Makoto; Kanda, Tatsuo; Oda, Shigeto; Yokosuka, Osamu
Abstract: Background: Corticosteroid (CS) has been introduced in most acute liver failure (ALF) patients for the purpose of suppressing pro‐inflammatory cytokines in Japan where a shortage of donor livers exists, whereas CS use is evaluated to be no benefit in Western countries. In the present study, we aimed to clarify the association between infectious complications and CS use in ALF, and determine when to evaluate treatment response and consider the timing for switching to liver transplantation (LT). Methods: Corticosteroid was administered to patients in the early stage prospectively. Clinical and biochemical features of 110 adult patients were analyzed. Results: Corticosteroids were administered to 78 (71%) patients. The duration between start of CS and onset of infection was 17 ± 10 days. Multivariate analysis revealed that infection was associated with age >50 years ( P = 0.034) and T‐BIL >15 mg/dl ( P < 0.001), and not with CS use ( P = 0.10). Accumulative incidence of infection was not different between patients with and without CS ( P = 0.18). Conclusions: Corticosteroid use did not significantly increase the incidence of infection. Two weeks after introduction of CS is a critical point for evaluating treatment response, avoiding infectious complications and switching to LT. Abstract : Highlight Aiming to clarify the association between infectious complications and corticosteroid use in acute liver failure, Yasui and colleagues showed that corticosteroid use did not significantly increase the incidence of infection and that two weeks after corticosteroid initiation was a critical point for evaluating treatment response and switching to liver transplantation.